New vectors of Rift Valley fever in West Africa. - Fontenille, D (Centers for Disease Control and Prevention, 1998)
After an outbreak of Rift Valley fever in Southern Mauritania in 1987, entomologic studies were conducted in a bordering region in Sénégal from 1991 to 1996 to identify the sylvatic vectors of Rift Valley fever virus. The virus was isolated from the floodwater mosquitoes Aedes vexans and Ae. ochraceus. In 1974 and 1983, the virus had been isolated from Ae. dalzieli. Although these vectors differ from the main vectors in East and South Africa, they use the same type of breeding sites and also feed on cattle and sheep. Although enzootic vectors have now been identified in West Africa, the factors causing outbreaks remain unclear.